The Application of e-Court as an Effort to Modernize the Justice Administration in Indonesia: Challenges & Problems - Pratiwi, Sahira Jati; Steven, Steven; Permatasari, Adinda Destaloka Putri (Faculty of Law, Universitas Negeri Semarang, 2020)
The Industrial Revolution 4.0 was an era marked by the carrying out of various technology-based human activities as a result of the transformation of life. This revolution has penetrated into various sectors of life, including the rule of justice. In order to face this revolution, the court is demanded to be able to provide legal services electronically through an application called e-Court. This application is an embodiment of The Electronic Justice System which has become a commitment of the Supreme Court of the Republic of Indonesia with the aim to synergize the role of information technology and procedural law. The presence of e-Court is expected to be able to overcome various problems in the Indonesian judicial process, such as the resolution of disputes that are running slowly, less responsive courts, and expensive judicial costs. Juridically, Law Number 48 of 2009 contains judicial principles. As stated in the law, cases submitted to the court must be resolved quickly, simply, and at a low cost. This means that the whole judicial process must be carried out with regard to effectiveness and efficiency in order to overcome obstacles in the justice administration. Thus, the presence of e-Court is expected to overcome various problems in the administration of justice with technology-based services. These services include online case registration, online case fee down payment, online party summons, and electronic trials. Therefore, this paper intends to describe the problems and challenges e-Court application in an effort to face the industrial revolution 4.0 in Indonesia.